Gambaran Standar Pelayanan Minimal Gizi di Ruang Rawat Inap Kelas III RSUD Dr. H. Slamet Martodirdjo Pamekasan - Nadiya Aulia Faza; Amalia Ruhana (Lembaga Pengembangan Kinerja Dosen, 2026)
Hospital nutrition services are an integral component of improving the quality of patient health. This descriptive observational study aims to evaluate the achievement of Minimum Service Standards (MSS) for nutrition at RSUD Dr. H. Slamet Martodirdjo Pamekasan, specifically focusing on the accuracy of diet types, timeliness of food distribution, and patient food waste. Data were collected over a single menu cycle (10 days) from November 24 to December 4, 2025, involving 44 patients per day. Research instruments included observation sheets and the Comstock visual method, with data analyzed based on the Decree of the Minister of Health (Kepmenkes) No. 129 of 2008. The results indicated that the timeliness of food distribution reached 96% and the accuracy of diet types reached 100%, both of which met the MSS requirements (≥ 90% and 100%, respectively). However, the average patient food waste was 25%, which does not yet meet the maximum standard of ≤ 20%. In conclusion, while logistical aspects have fulfilled the established standards, the hospital needs to conduct further evaluations regarding food flavor factors and patients' clinical conditions to reduce food waste in accordance with the applicable standards.